Play Among Books : A Symposium on Architecture and Information Spelt in Atom-Letters - _ch3n81, Alice (2021)
How does coding change the way we think about architecture? Miro Roman and his AI Alice_ch3n81 develop a playful scenario in which they propose coding as the new literacy of information. They convey knowledge in the form of a project model that links the fields of architecture and information through two interwoven narrative strands in an "infinite flow" of real books.